Cerebral Ischemia-Reperfusion Induced Neuronal Damage, Inflammation, miR-374a-5p, MAPK6, NLRP3, and Smad6 Alterations: Rescue Effect of N-acetylcysteine - Hamed Saniei; Alireza Shirpoor; Roya Naderi (Tabriz University of Medical Sciences, 2024)
Background: Ischemic stroke (IS) is still a major cause of neurological disability. This study aimed to ascertain potential markers closely related to IS diagnosis and treatment and then we examined the neuroprotective effect of N-acetylcysteine (NAC) in a transient cerebral ischemia. Methods: Male Wistar rats were randomly divided into three groups (n=6), including sham, IR (ischemia-reperfusion), IR+NAC (150 mg/kg, ip; intraperitoneally, 1 hour prior to ischemia and 5 min before reperfusion). The infarct volume was evaluated by 2,3,5-triphenyl tetrazolium chloride staining. H&E and Nissle staining were performed to evaluate cerebral ischemia-reperfusion injury. miR-374a-5p gene expression, MAPK6, NLRP3, smad6, TNF-α, and IL-1β protein levels were determined by Real-time PCR, Western blot, and Elisa in the cerebral cortex exposed to IR. Results: Herein, we found that IR increased infarct volume and pathological damage to the cerebral cortex after global cerebral artery occlusion/reperfusion. In addition, miR-374a-5p gene expression decreased, while MAPK6, NLRP3, and smad6 protein expressions increased in the IR group. TNF-α and IL-1β protein levels increased in the ischemic cortex. Treatment with NAC significantly attenuated infarct size, inflammation and reversed aforementioned molecule levels. Conclusion: Taken together, these results suggested that ischemic insult can increase infarct size, neuronal damage, and inflammation may in part by modulating miR-374a-5p, MAPK6, NLRP3, and smad6 pathway in the brain cortex after cerebral IR insult and providing new clues to molecular mechanisms and treatment targets in IS. It can be alleviated by NAC as a potential therapy for someone afflicted with ischemia.